2022
DOI: 10.3389/froh.2022.838043
|View full text |Cite|
|
Sign up to set email alerts
|

Irrigating Solutions and Activation Methods Used in Clinical Endodontics: A Systematic Review

Abstract: BackgroundEx vivo and in vitro studies have demonstrated the effectiveness of some irrigation protocols in reducing the bacterial load in the root canal system. However, standardized protocols have not yet been defined for the real clinical context due to many irrigation procedures available.ObjectiveTo evaluate the clinical endodontic protocols and limitations of irrigating solutions in the disinfection of the root canal system in patients with apical periodontitis.MethodsPubMed, Scopus, Embase, Web of Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 91 publications
(130 reference statements)
0
37
0
2
Order By: Relevance
“…Root canal preparation is one of the most critical parts of successful endodontic treatment, and this step is essential in two aspects, including cleaning and shaping the root canal and cleaning tissue debris and root canal irrigation to remove and debride the root canal and disinfect the root canal system ( 1 , 2 ). Various chemical solutions are being introduced and widely used ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Root canal preparation is one of the most critical parts of successful endodontic treatment, and this step is essential in two aspects, including cleaning and shaping the root canal and cleaning tissue debris and root canal irrigation to remove and debride the root canal and disinfect the root canal system ( 1 , 2 ). Various chemical solutions are being introduced and widely used ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it has been shown that because of morphological limitations, a significant percentage of the root canal wall areas (35%-53%) might be untouched during root canal instrumentation ( 2 ). To compensate for this shortcoming, root canal irrigation methods have been introduced to clean, disinfect or remove the smear layer based on the following strategies: irrigation and disinfection of the canal system with a conventional syringe and activating the irrigating solution during the irrigation process ( 2 ). The activation of the irrigants can increase the chemical and physical effects of the solution in the irrigation process due to the greater twitching and dispersion of the solution in the root canal system ( 2 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a lengthy procedure in which the tooth is mechanically and chemically cleaned of bacteria and pulpal remnants, shaped into canals and then sealed into the canal system along with restoration of the coronal portion to prevent future reinfection. 1,2 This is usually done in multiple appointments. At the end of each visit, intracanal medicament with a temporary filling is placed.…”
Section: Introductionmentioning
confidence: 99%
“…Most endodontic infections are treated by chemo-mechanical preparation, however, about 35-60% of the root canal walls remain intact [1,2]. Thus, failure of root canal treatment has been predominantly associated with an ineffective elimination of microorganisms in a planktonic state and biofilm, which are present in the entire root canal system [3][4][5]. Moreover, the development of apical periodontitis has also been observed in some apparently well endodontically treated teeth.…”
Section: Introductionmentioning
confidence: 99%